Morphological and immunocytochemical characterization of snake-like chromatin cells - Jirsova, K; Juklova, K; Vesela, V; Filipec, M (Histology and histopathology, 2006)
Snake-like chromatin (SLC) is a nuclear alteration occurring under various pathological conditions and in different tissues. The aim of this study was the morphological and immunocytochemical characterization of SLC-positive conjunctival epithelial cells from keratoconjunctivitis sicca (KCS) patients. Impression cytology specimens from the upper bulbar conjunctiva of 10 controls and 10 KCS patients with a high incidence of SLC cells were assessed, the morphology of SLC nuclei evaluated by light microscopy, and proliferation markers, nucleolar proteins, lamins and cytokeratin filaments detected immunocytochemically. In KCS patients, SLC cells with a normal nuclear shape, with nuclear membrane notching (2.3% of cells) and with binuclear dumb-bell structures (4.4% of cells) were observed. The most striking features of SLC cells were the absence of an A/C lamin signal, the redistribution of fibrillarin into two spots adjacent to SLC structures and cytokeratin 14 positivity in the strangulation belt of the dumb-bell structures. The deficiency of lamin A/C is the probable reason for the disintegration of chromatin from the nuclear lamina in SLC cells. The occurrence of SLC-positive cells, SLC-positive dumb-bell shaped nuclei and SLC-positive binucleated cells, together with the absence of mitotic markers, leads to the conclusion that the SLC phenomenon might be a form of nuclear segregation.
Keywords: jaderný obal; Cell Division; keratiny; Lamin Type B; Humans; konjunktiva; Cell Nucleus; lidé středního věku; lamin typ B; Female; dospělí; Keratoconjunctivitis Sicca; jaderné proteiny; buněčné jádro; chromatin; lidé; proliferace buněk; Immunohistochemistry; suchá keratokonjunktivitida; imunohistochemie; Chromatin; Adult; fluorescenční protilátková technika nepřímá; ženské pohlaví; Lamin Type A; Male; Middle Aged; Cell Proliferation; Nuclear Proteins; regenerace; Nuclear Envelope; Fluorescent Antibody Technique, Indirect; lamin typ A; mužské pohlaví; Conjunctiva; Keratins; Regeneration; buněčné dělení